Welfare comparisons between societies with different population sizes and environmental characteristics - Geir B. Asheim (University of Oslo, Department of Economics, 2005)
To provide a normative foundation for transfers between different societies, one needs information on the “per capita welfare” in different societies, having different population sizes and environmental characteristics. This paper reviews various methods for doing such comparisons. The main conclusion of the analysis is that there appears to be no practical alternative to applying real comprehensive per capita NNP. This is a per capita variant of Weitzman's stationary welfare equivalent of future utility. Welfare comparisons between different societies must be made in local real prices calculated according to “purchasing-power-parity”, where non-traded environmental amenities may play an important role.
Keywords: D60; D90; O47; 330; National accounting; Population; Dynamic welfare; Volkswirtschaftliche Gesamtrechnung; Bevölkerung; Wohlfahrtstheorie; Intertemporale Allokation